Developing Core Competencies for Islamic Higher Education in Indonesia in the Era of Industrial Revolution 4.0 - Alhamuddin, Alhamuddin; Andi Murniati; Eko Surbiyantoro; Dewi Mulyani (Jurnal Pendidikan Islam Indonesia, 2021)
The curriculum has a role as an instrument to conserve the culture of a nation. Without a good curriculum, the culture of a nation can be extinct right away because there are no preservation efforts. By way of inclusion of culture in the curriculum, it is hoped that it can be passed on to the next generation. Then they will know at least their ancestors’ culture. It is called a conservative role. This research uses a quantitative approach with a case study method. Data collection was carried out by a questionnaire and in-depth interviews. Data were analyzed using an interactive model. This analysis technique started from data collection. Data was reduced after it had been collected. The next step was to presenting the data, verifying and drawing a conclusion. Based on the description above, this research is considered important to be carried out being an addition for existing policymakers in order to organize higher education. Moreover, it is in response to the demands and basic guidance of compiling a curriculum based on the Indonesian National Qualifications Framework (KKNI) which is being and will be implemented in higher education in Indonesia especially in Islamic colleges.